PENGEMBANGAN SISTEM INFORMASI BERBASIS WEB PADA PROGRAM STUDI PENDIDIKAN FISIKA UNIVERSITAS NUSA CENDANA - Jannes Bastian Selly; Nikodemus Umbu Janga Hauwali; Vinsensius Lantik; Marsi D. S. Bani (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
The Physics Education study program, Nusa Cendana University, already has a web-based study program information system but it has not been managed optimally, as evidenced by the limited availability of study program data on the web. This study aims to identify the data needed to be developed into useful information, not only for the academic community of the Physics Education undergraduate study program, Nusa Cendana University, but for society in general. The method used is to carry out an issue analysis based on APKL and USG techniques. The results of the identification of issues were then consulted with stakeholders, in this case the dean of the Teaching and Education Faculty, and the coordinator of the Physics Education Study Program. The data obtained is then made into a graphic design or linked to a menu available on the web, so that it becomes useful information. Keywords : Web-based information system, physics education study program, Nusa Cendana University